Static Threshold Pressure Gradient Characteristics of Liquid Influenced by Boundary Wettability - 宋付权 汪建东 刘海丽 (Chinese physics letters, 2010)
We propose an experimental setup to measure the threshold pressure gradient （TPG） of microchannels with different wettability surfaces by the static method in microchannels with diameters from 20 μm to 320 μm, and compare the TPG of microchannels with adsorption of cetyl trimethyl ammonium bromide （CTAB） with that without CTAB adsorption. The results show the existence of TPG in microchannels. The TPG of microchannels increases with decreasing hydrodynamic diameter, and the relation between TPG and diameter is in agreement with the single-log normalization. The TPG of a microchannel with CTAB adsorption decreases obviously as compared with the microchannel without CTAB adsorption. The TPG of microchannels with different wettabilities of boundary surface are different, and the resistance of liquid flow can be reduced by changing the wettability of boundary surfaces.